Molecular Characterization of Extended-Spectrum β-Lactamase-Producing Multidrug Resistant Escherichia coli From Swine in Northwest China - Liu, Xiaoqiang; Liu, Haixia; Wang, Le; Peng, Qian; Li, Yinqian; Zhou, Hongchao; Li, Qinfan (Frontiers in Microbiology, 2018)
Objectives: The aim of the present study was to explore the prevalence and molecular characterization of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli collected from pig farms in Northwest China. Methods: Between May 2015 and June 2017, a total of 456 E. coli isolates were collected from fecal samples of healthy and diarrheal pigs in Northwest China to screen the ESBL producers. The β-lactamases, plasmid-mediated quinolone resistance (PMQR) genes and virulence genes among ESBL producers were corroborated by PCR and sequencing. Finally, ESBL producers were further grouped according to phylogenetic background and genetic relatedness. Results: Forty-four (9.6%) out of the 456 E. coli isolates were identified as ESBL-producing isolates. All ESBL producers exhibited multidrug resistance (MDR) phenotype, and more than 90% of the ESBL producers were resistant to amoxicillin, amoxicillin-clavulanic acid, oxytetracycline, enrofloxacin and sulfamethoxazole/trimethoprim. All ESBL producers harbored at least one type of β-lactamase, with blaCTX-M, blaTEM, blaSHV, blaOXA-48 and blaKPC-2 being detected in forty, thirty, seven, four, two and one isolates, respectively. Sequencing revealed the most common blaCTX-M subtype was blaCTX-M-14 (n=24), followed by blaCTX-M-15 (n=14), blaCTX-M-64 (n=11), blaCTX-M-9 (n=10) and blaCTX-M-123 (n=9). qnrS (n=23) was the predominant PMQR gene, and all PMQR genes were detected in co-existence with β-lactamase genes. estA (n=18) and F4 (n=18) were the most prevalent enterotoxin and fimbrial adhesin, respectively, and 27 different virotypes were found with respect to the association of enterotoxins and fimbrial adhesins. Twenty-four different sequence types (STs) were identified among 44 ESBL producers, and clones ST405, ST10 and ST648 were strongly present in more than one-third (34.1%) of ESBL producers. Conclusion: All ESBL-producing E. coli isolates exhibited MDR phenotype, and showed high prevalence of β-lactamase and PMQR genes. Especially, one isolate harbored ESBL genes blaTEM, blaSHV, blaCTX-M-9, blaCTX-M-14, blaCTX-M-64 and carbapenemase gene blaOXA-48 and blaKPC-2, as well as PMQR genes qnrS, qnrB, qnrD, qepA and aac(6')-Ib-cr.